Penerapan Database Persediaan Dan Data Pasien Berbasis Microsoft Access Dalam Rangka Meningkatkan Efisiensi Operasi Pada Puskesmas Sukaharja - Hastoni, Hastoni (STIE Kesatuan, 2010)
Sukaharja Public Health Center is under the health office of Bogor regency. In the beginning, there was no public health center in Sukaraja. Due to health service need of the society increased, Bogor regency government decided to establish public health center in Sukaraja. Together with the fact that public health service grew rapidly, itâs needed a system having capacity to handle all activities at public health center. Thereby, the author can write concerning implementation of inventories database and patients data in microsoft access based. The purpose of this research is to find out the recording system of inventories and patients data and how the inventories database and patients data have been applied at Sukaraja public health center. The research was carried out by the author at Sukaraja Public Health Center located in Jl. Pondok Bitung No. 190, Sukaraja, Cijeruk, Bogor 16740. This public health center has main activity, that is to provide health services to all members of Sukaraja society, especially those who are poor. To find data and information, the author utilizes field and library research by observing directly to the researh object spot and some literatures supporting the subject matter. Recording system of medicine stock and patients data has close connection with operational activity of the public health.Public health center receive medicine from three sources, those are regencyâs budget and revenue (APBD), health insurance (ASKES), and public health guarantee (JAMKESMAS). Whereas, the patients of public health center are devided into four kinds, namely general patients, health insurance (ASKES) patients, public helath guarantee (JAMKESMAS) patients, and free of charge patients.Supply system and data of Sukaraja Public Health Center are still recorded manually. Manually data archives in the form of paper and the like can result in significant risk and furthermore it causes the important data will be lost. Itâs needed a system which is able to save data safely. The necessity of data which is efficient, effective, fast, and easily obtained when itâs needed becomes main reason to providing information appropriately. Due to that fact, the author makes title âThe Implementation of Inventories Database and patients Data in Mocrosoft Access Based in Increasing Operation Efficiencyâ. By this implementation it can be expected to overcome all necessities needed, specifically in making reports so that the services povided can be fast, smooth, and qualified with the result that the operation will be efficient